Analisis Manajemen Risiko pada Pekerja Pabrik yang ada di Kabupaten Brebes - Dila Lailatul Munawaroh; Amirah (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
The manufacturing industry in Brebes Regency employs a large workforce and has high occupational safety and health risks, requiring the implementation of systematic risk management. This study aims to analyze the implementation of risk management among factory workers in Brebes Regency based on the stages of risk identification, measurement, and management. The study used a quantitative descriptive approach with 100 respondents from three companies. Data were collected through a five-point Likert questionnaire consisting of 39 statements and analyzed using average scores with categories of Poor (1.00–<2.50), Fair (2.50–<3.50), and Very Good (3.50–5.00). The results show that the average indicator value is in the range of 3.96–4.71, so that all indicators are in the Very Good category, with an average risk identification aspect of 4.48, risk measurement of 4.43, and risk management of 4.50. The highest scores were for recording personal property loss (4.71) and awareness of noise hazards (4.56), while the lowest scores were for assessing muscle complaints/minor injuries due to work posture (3.96) and work position and short break arrangements (4.33). Overall, the implementation of risk management has been very good, but strengthening of the ergonomics aspect is still needed through more formal recording of complaints, periodic observation of posture and workload, and ergonomic interventions so that the implementation of risk management is more balanced and sustainable.